With no direction home - Finkelstein, Marni (Thomson/Wadsworth, 2005)
This book gives voice to the homeless youth and is rich with material on their everyday lives, including living conditions and street experiences. The case study's strength lies in its ethnographic methodology, which combines direct observations and qualitative interviews. Ethnography is particularly important in describing populations and social environments that are hidden from normal observation, and is indispensable when exploring emerging phenomena, such as the formative fictive kin networks among street youth, or new ways of looking at drug addiction. Finkelstein discusses her own experiences with the street kids, including how she was able to develop a rapport within the "street scene